Prevalence and Distribution of Pulp Stones in a Group of Peruvian Adults: a Cone Beam Computed Tomography Study - Calero-Hinostroza, Gisella G.; Tinedo-López, Pedro L.; García-Rupaya, Carmen R. (Odovtos - International Journal of Dental Sciences, 2020)
The aim of this study was to evaluate the prevalence and distribution of pulp stones in a group of Peruvian adults using cone beam tomography (CBCT). Materials and methods: 60 randomly selected CBCT from a tomographic center in Lima, Peru were analyzed. A total of 1263 images of teeth using the Point 3D Combi 500 S tomograph were evaluated. Images analysis was performed with Real Scan software and all teeth were evaluated in sagittal, axial and coronal views. All measurements were subjected to a chi square test. (p<0.05). Results: Of the 1263 teeth, 30.8% presented pulp calcifications through the CBCT. The prevalence of calcifications was higher in women than in men. The maxillary and mandibular molars were the groups of teeth with the highest frequency of pulp stones. There was significance between the pulp stones and the gender, age range, type and state of the tooth. Conclusions: The maxillary first molars had a higher prevalence of pulp calcifications than the mandibular ones. The presence of caries increased the possibility of the appearance of these calcifications, specifically in the maxillary teeth. CBCT could be a sensitive tool to detect pulp stones. Knowledge of the distribution of pulp stones can help dentists in the clinical treatment of endodontics.